2007
DOI: 10.1159/000106351
|View full text |Cite
|
Sign up to set email alerts
|

Multiple True Umbilical Knots: A Silent Risk for Intrauterine Growth Restriction with Anomalous Hemodynamic Pattern

Abstract: True knots of the umbilical cord can represent a serious complication for the fetus due to the possible alteration in the fetal circulation with consequent intrauterine growth restriction or fetal death. We report a case of 5 true umbilical cord knots associated with severe fetal growth restriction and an abnormal hemodynamic pattern. The Doppler examination showed a hemodynamic pattern characterized by an early alteration in the waveform profile in the fetal venous districts with normal impedance to flow valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Predanic et al [23] suggested that HCC could be rather more prone to cord torsion than to compression or stretching that would adversely affect blood flow, such as in the experimental model that demonstrated that less encirclement force was required to occlude venous perfusion in cords that had more coils [24] . In these respects, the umbilical Doppler changes described by Predanic et al [23] would be similar to those reported for cases with true knots of the umbilical cord [25] . Therefore, in cases with HCC various complications would frequently occur during labor probably due to a smaller amount of WJ.…”
Section: Discussionsupporting
confidence: 82%
“…Predanic et al [23] suggested that HCC could be rather more prone to cord torsion than to compression or stretching that would adversely affect blood flow, such as in the experimental model that demonstrated that less encirclement force was required to occlude venous perfusion in cords that had more coils [24] . In these respects, the umbilical Doppler changes described by Predanic et al [23] would be similar to those reported for cases with true knots of the umbilical cord [25] . Therefore, in cases with HCC various complications would frequently occur during labor probably due to a smaller amount of WJ.…”
Section: Discussionsupporting
confidence: 82%
“…Despite the relatively high incidence of true knots of the umbilical cord at birth and the increased risk of stillbirth,2, 4 a prenatal diagnosis is infrequently reported 3. Different sonographic findings have been proposed as characteristic of true knots, although none of them has been reported to be specific for the diagnosis 5.…”
Section: Discussionmentioning
confidence: 99%
“…Once the prenatal diagnosis of a true knot is highly suspected, the management of the case has to be prudent, given the increased risk of intrauterine fetal demise,1, 2 and adequate counseling has to be offered to parents. Close monitoring of the pregnancy is mandatory, mainly based on umbilical artery Doppler velocimetry until term, and continuous cardiotocography during labor is recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sonography has allowed for the in vivo detailed observation of the morphologic characteristics and hemodynamics of the umbilical cord in cases of a true knot of the umbilical cord [1][2][3][4][5][6][7] as well as for insights into the relevance of this antenatal finding. 8,9 Indeed, the fetoplacental circulation can be compromised by a true knot of the umbilical cord, leading to fetal demise.…”
mentioning
confidence: 99%